You also may approach the equation using factorization, such that:

`cos theta*(1 - tan theta) = 0`

Using zero product rule yields:

`{(cos theta = 0),(1 - tan theta = 0):} `

Since none of the answer provided does not include a value for theta that satisfies the equation `cos...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You also may approach the equation using factorization, such that:

`cos theta*(1 - tan theta) = 0`

Using zero product rule yields:

`{(cos theta = 0),(1 - tan theta = 0):} `

Since none of the answer provided does not include a value for theta that satisfies the equation `cos theta = 0` , hence, only `1 - tan theta = 0` , such that:

`1 - tan theta = 0 => -tan theta = -1 => tan theta = 1`

Since the tangent function is positive in quadrants 1 and 3 yields that `theta` can have the following values:

`theta = pi/4` (quadrant 1)

`theta = pi + pi/4 = (5pi/4)` (quadrant 3)

**Hence, evaluating the correct answer among the options provided yields that option `D) pi/4, (5pi/4)` is valid.**

**Further Reading**

First simplify the problem:

`tantheta=sintheta/costheta`

`costheta-(sintheta/costheta)costheta=0`

`costheta-sintheta=0`

`costheta=sintheta `

The values for which cosine equals sine are pi/4 and 5pi/4; threfore, the answer is d)